100 Days of marine Synechococcus–Ruegeria pomeroyi interaction: A detailed analysis of the exoproteome. (15th December 2017) - Kaur, Amandeep; Hernandez‐Fernaud, Juan R.; Aguilo‐Ferretjans, Maria del Mar; Wellington, Elizabeth M.; Christie‐Oleza, Joseph A.
Summary: Marine phototroph and heterotroph interactions are vital in maintaining the nutrient balance in the oceans as essential nutrients need to be rapidly cycled before sinking to aphotic layers. The aim of this study was to highlight the molecular mechanisms that drive these interactions. For this, we generated a detailed exoproteomic time‐course analysis of a 100‐day co‐culture between the model marine picocyanobacterium Synechococcus sp. WH7803 and the Roseobacter strain Ruegeria pomeroyi DSS‐3, both in nutrient‐enriched and natural oligotrophic seawater. The proteomic data showed a transition between the initial growth phase and stable‐state phase that, in the case of the heterotroph, was caused by a switch in motility attributed to organic matter availability. The phototroph adapted to seawater oligotrophy by reducing its selective leakiness, increasing the acquisition of essential nutrients and secreting conserved proteins of unknown function. We also report a surprisingly high abundance of extracellular superoxide dismutase produced by Synechococcus and a dynamic secretion of potential hydrolytic enzyme candidates used by the heterotroph to cleave organic groups and hydrolase polymeric organic matter produced by the cyanobacterium. The time course dataset we present here will become a reference for understanding the molecular processes underpinning marine phototroph‐heterotroph interactions.